Improving end-to-end communication by novel methodology of route quality approximation. (2nd October 2018) - Prčić, Vjekoslav-Leonard; Kalpić, Damir; Šimunić, Dina
ABSTRACT: With the number of wireless smart devices growing rapidly due to the constant technological advances and product availability, significant effort has been put into optimizing their functioning to achieve the best possible performance. Using a wireless device usually implies them having an integrated power supply, and often without a possibility of recharging it. To mitigate the devices running out of power too soon, there is a myriad of developed approaches. One of the approaches is to use a low-consumption data exchange protocol, such as Zigbee that relies on the short-range devices to construct a wireless personal area network and use it to relay messages. To route packages through the network, the Zigbee protocol uses the ad-hoc on-demand distant vector routing protocol. In this paper, we analyse two new versions of a modified ad-hoc on-demand distant vector routing protocol that define routes by maximizing a route quality measure based upon aggregated link quality approximations.